Markers of collagen metabolism and insulin-like growth factor binding protein-1 in term infants. Issue 1 (1st July 2000) - Hytinantti, T; Rutanen, E-M; Turpeinen, M; Sorva, R; Andersson, S
Abstract : AIM: To study the relation between fetal growth and markers of collagen metabolism and insulin-like growth factor binding protein-1 (IGFBP-1) in term infants. METHODS: Cord vein plasma was obtained from 67 term infants of gestational age 37.1–41.7 weeks (39 appropriate for gestational age (AGA), 11 large for gestational age (LGA; relative birth weight ⩾ 2.0 SD), and 17 small for gestational age (SGA; relative birth weight ⩽ −2.0 SD)) for analysis of markers of metabolism of collagen type I (PICP and ICTP) and III (PIIINP) and of IGFBP-1. RESULTS: Negative correlations existed between gestational age and PICP ( r = −0.294, p = 0.0158), ICTP ( r = −0.338, p = 0.0052), and PIIINP ( r = −0.432, p = 0.0003). These correlations were also found in SGA infants (all p < 0.05). IGFBP-1 showed negative correlations with birth weight and relative birth weight ( r = −0.644, p = 0.0001, and r = −0.693, p = 0.0001 respectively) but not with gestational age (p>0.05). CONCLUSIONS: In the term fetus, collagen metabolism is primarily dependent on maturity and not on intrauterine growth status, whereas IGFBP-1 reflects intrauterine growth independently of maturity.